Potret Kepatuhan Perpajakan Wajib Pajak Profesi Notaris - Su'adah, Su'adah; Faisol, Moh. (Universitas Bina Sarana Informatika, 2024)
The notary profession is one of the professions that has a low level of compliance, which is ± 39% other than lawyers and curators. This study aims to determine the tax compliance of taxpayers who work as notaries,